2020
DOI: 10.1017/s0954102020000085
|View full text |Cite
|
Sign up to set email alerts
|

Gone fishing: Adélie penguin site-specific foraging tactics and breeding performance

Abstract: The ecological drivers underlying breeding performance are expected to differ across the geographical range of seabird species, but few studies have compared trade-offs between colonies with different local conditions. During chick-rearing (2000–01), we compared the foraging trips, diet and breeding parameters of two Adélie penguin colonies in the Ross Sea, at Edmonson Point (EdPo; ~2000 breeding pairs) and Inexpressible Island (InIs; ~24 000 breeding pairs). Penguins from InIs travelled farther and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
5
13
0
Order By: Relevance
“…Skua predation is the major cause of egg and chick loss, accounting for up to 40% during the breeding season (S. Olmastroni, unpublished data 1996–2018). However, breeding success, diet, foraging range and adult survival rate for the Edmonson Point population are similar to those of other colonies (Ballerini et al 2009, Olmastroni et al 2020) and other parts of the Antarctic (Jenouvrier et al 2006). Immature pre-breeders are important to population demography (Bicknell et al 2014), although Ballerini et al (2009) reported a low recruitment of birds marked as chicks (25%) for this colony.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Skua predation is the major cause of egg and chick loss, accounting for up to 40% during the breeding season (S. Olmastroni, unpublished data 1996–2018). However, breeding success, diet, foraging range and adult survival rate for the Edmonson Point population are similar to those of other colonies (Ballerini et al 2009, Olmastroni et al 2020) and other parts of the Antarctic (Jenouvrier et al 2006). Immature pre-breeders are important to population demography (Bicknell et al 2014), although Ballerini et al (2009) reported a low recruitment of birds marked as chicks (25%) for this colony.…”
Section: Discussionsupporting
confidence: 77%
“…Killer whales ( Orcinus orca , ecotype B) have been observed travelling along the fast-ice edge and shoreline among the Wood Bay and TNB area (Lauriano et al 2011). A previous study showed that the penguins fed little inside the TNB polynya area, but rather used it to reach the pack ice that rings the polynya, rather than to walking (Olmastroni et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of krill and P. antarctica as prey for penguins is related to sea ice dynamics (Ainley et al 1998). In fact, increased availability of krill as prey for penguins seem to occur in seasons or areas characterized by a greater pack ice presence while there is an increase in fish availability in areas without sea ice (Ainley et al1998(Ainley et al , 2003Strickland et al, 2008;Olmastroni et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…If sexual dimorphism in bill size was due to sexual selection, one could speculate that a lower sexual selection on bill size may have occurred because of the relatively low habitat quality at Edmoson Point. In this colony, persistent fast-ice and high density of terrestrial predators (South Polar Skua Stercorarius maccormicki) seem to increase energetic constraints of penguins (see Clarke et al 1998;Olmastroni et al 2004Olmastroni et al , 2020Pezzo et al 2007;Mori et al 2021, for environmental-related constraints at Edmonson Point), which might have reduced the potential investment in sexual selection. Nevertheless, this hypothesis remains to be tested across colonies differing in habitat quality/predator density.…”
Section: Discussionmentioning
confidence: 93%